Microstructure of the human metastatic vertebral body - Cavazzoni, Giulia; Dall’Ara, Enrico; Palanca, Marco (Frontiers in Endocrinology, 2025)
IntroductionBone spinal metastases disrupt the bone homeostasis, inducing a local imbalance in the bone formation and/or resorption, with consequent loss of the structural optimisation of the vertebrae and increase of the risk of fracture. Little is known about the microstructure of the metastatic tissue, the microstructure of the tissue surrounding the lesion, and how it does compare with vertebrae with no lesions observed on the biomedical images. A comprehensive assessment of the microstructural properties of the entire vertebral body can be obtained with micro computed tomography. In this study, we evaluated to what extent the vertebral body is affected by the presence of a metastatic lesion, the properties of the metastatic lesions, and whether the tissue surrounding the lesion has microstructural features similar to those of healthy tissue.MethodsA total of 30 metastatic vertebrae, including lytic (N = 12), blastic (N = 10), and mixed (N = 8) metastases, and 20 control vertebrae with no visible lesions on computed tomography were scanned using micro computed tomography (voxel size = 39 mm). The images were segmented and analysed to evaluate the microstructural properties in the entire vertebral body, in the lesion, and in the bone surrounding the lesion.ResultsThe microstructural properties evaluated on the entire vertebral bodies showed remarkable differences between metastatic and control vertebral bodies (p < 0.034) in terms of bone volume fraction, trabecular thickness, degree of anisotropy, connectivity density, and trabecular pattern factor. On the other hand, when the tissue surrounding the lesion was considered, no differences were found between metastatic and control vertebral bodies, except for differences in the degree of anisotropy (p = 0.008). All microstructural parameters measured in the regions including the lytic or the blastic metastases significantly differed (p < 0.001) from those in the tissues surrounding the lesions. The lytic lesions minimally affected the regions closest to the metastases, with significant differences only in the connectivity density. On the other hand, blastic metastases also affected the trabecular separation, the bone surface density, and the connectivity density in the closest tissue surrounding the lesion.DiscussionMost of the microstructural features of the trabecular bone in metastatic vertebrae were locally affected by lytic and blastic metastases, whereas the surrounding tissue showed a microstructure similar to that of adjacent vertebrae without visible lesions